2018
DOI: 10.1007/s10686-018-9572-7
|View full text |Cite
|
Sign up to set email alerts
|

The ARIEL mission reference sample

Abstract: The ARIEL (Atmospheric Remote-sensing Exoplanet Large-survey) mission concept is one of the three M4 mission candidates selected by the European Space Agency (ESA) for a Phase A study, competing for a launch in 2026. ARIEL has been designed to study the physical and chemical properties of a large and diverse sample of exoplanets, and through those understand how planets form and evolve in our galaxy.Here we describe the assumptions made to estimate an optimal sample of exoplanets -including both the already kn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…To generate an indicative core mission sample observable by ARIEL in 2028 during its four year mission, a list of targets with different stellar types (F, G, K, M) and planetary parameters (size: Jupiters, Neptunes, sub-Neptunes, super-Earths, Earth-size; different temperatures) has been created [264]. This list was compiled using the statistics provided by the NASA Kepler mission combined with the number/types of stars in the Solar neighbourhood (Fressin et al [85]).…”
Section: Ariel Tier 1: Exoplanet Population Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…To generate an indicative core mission sample observable by ARIEL in 2028 during its four year mission, a list of targets with different stellar types (F, G, K, M) and planetary parameters (size: Jupiters, Neptunes, sub-Neptunes, super-Earths, Earth-size; different temperatures) has been created [264]. This list was compiled using the statistics provided by the NASA Kepler mission combined with the number/types of stars in the Solar neighbourhood (Fressin et al [85]).…”
Section: Ariel Tier 1: Exoplanet Population Analysismentioning
confidence: 99%
“…33). From Zingales et al [264]. Left: spectral types and metallicity of the stars hosting the planet candidates observable by ARIEL in Tier 1 modality (Pillitteri and Micela [178]) available (see e.g.…”
Section: Ariel Tier 1: Exoplanet Population Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A static radiometric model was used to determine the signal-to-noise achievable for transit and occultation observations of individual and samples of targets. Based on conservative assumptions of the achievable mission/instrument performance, as appropriate to study phase, it was shown that the requirements on the numbers and diversity of targets in the ARIEL core sample could readily be met [5]. Known targets already make up a diverse sample of exoplanets and host stars, with a pool from which the targets could be drawn that will continue to increase in breadth and number with the results of ongoing ground-based and space-based surveys as well as future planned space missions, in particular by the NASA TESS mission, to be launched in early 2018 [6].…”
Section: The Target Listmentioning
confidence: 99%